Does Early Intravenous Infusion of Magnesium Sulfate Play a Role in the Management of Neonatal Hypoxic-Ischemic Encephalopathy? - جوني, عدي (Latakia University Journal -Medical Sciences Series, 2020)
One of the most important causes of mortality and morbidity in neonates is perinatal asphyxia, as it ranks third as the cause of death in neonates. Until now, there is no treatment to fully protect of neurological consequences of perinatal asphyxia. Results of studies conducted on magnesium sulfate (MgSO4) that have not been definitively proven to be a preventative treatment for hypoxic-ischemic encephalopathy (HIE). The aim of our research was to study the effect of the (MgSO4) on the management of HIE, by recording an occurrence of seizures and controlling them with one anticonvulsant, initiation time for oral feeding, neurological examination at graduation, and mortality rate, compared to patients who were managed without applying it.. The sample included 42 patients, from the newborns admitted to the neonatal Department, at Tishreen University Hospital during the period (2016-2017). The drug (MgSO4) was applied intravenously at a dose of 200 mg/kg/day, Within 3 days, or placebo (Normal Saline), was applied randomly according to the random schedule, so that the study (treatment) sample included 22 patients, and the control (placebo) sample 20 patients. No statistical significance was observed in the distribution of seizures prior to the application of the drug combination between the two groups, but the response rate to one anticonvulsant was better in the treatment group (63.63% versus 33.33%), this difference was not statistically significant. We noticed that there were statistically significant differences with regard to the start time of feeding by the nasal gastric tube (NGT), and the time of initiation of feeding by sucking between the two groups (0.05>p value), where the mean start time for NGT was 2 days faster than in the placebo group. (5.2 days versus 6.87 days), and the average time to start feeding with sucking was approximately 6 days faster in the treatment group than in the placebo group (11 days versus 17 days). We found that the proportion of neonates who received their full need from nutrition by sucking was higher in the treatment group (68.18% vs. 35%). (p 0,05>), although the number of deaths was lower in the treatment group (4 out of 22 neonates), and (6 out of 20 neonates) in the placebo group (18% versus 30%), but this difference was not statistically significant. Neurological examination was considered acceptable upon discharge from the hospital with at least two of the three normal criteria of clinical neurological examination being available (muscle tone, reflex Moro, sucking reflex), the result was better in the treatment group (77.78% vs. 35.71%) (p value = 0.016).Our study also showed that The application of (MgSO4) in a dose of (200 mg/kg) was effective and safe, no side effects were observed when it is leaked to newborns.